Corneal Ectasis among Wrestlers: Report of Two Cases - Mohammad Ali Zare Mehrjardi; Hadi Zare Mehrjardi; Abasali Gaeeni; Elham Ashrafi; Homa Naderifar (The Society of Aging and Physical Activity (SAPA), 2014)
Report keratoconus in two patients with a long history of wrestling without any risk factor for corneal ectasia and reviewing the possible pathogenesis. To confirm suspicion of keratoconus, corneal topography was performed using scanning slit topography system and Orbscan. In two wrestlers with the complaint of visual loss in their eyes and IOP raising, corneal topography was performed and development of keratoconus (KCN) was detected. Athletes involved in sports with high strenuous exercises might need routine eye examination and also a baseline corneal topography. This may provide an earlier detection of KCN in this group of athletics.